Genetic diversity of the Hungarian draft horse assessed by mitochondrial DNA - Csizmár, Nikolett; Mihók, Sándor; Jávor, András; Kusza, Szilvia (Acta Agraria Debreceniensis, 2016)
Hungarian draft is a horse breed with a recent mixed ancestry. It was developed in the 1920s by crossing local mares with draught horses imported from France and Belgium. To genetically characterize the breed and to set up the basis for a conservation programme, we have employed a molecular marker: a 256-bp D-loop mitochondrial DNA fragment. We analyzed 124 horses representing Hungarian draft horses to assess the maternal phylogeography of the breed. Sequence analysis of a 256-bp segment revealed a total of 34 haplotypes with thirty-four polymorphic sites. High haplotype and nucleotide diversity values (Hd=0.953±0.001; π=0.024±0.001) were detected. The average number of pairwise differences were k=5.998. This breed counts 800 mares today, and only survive due to breeding programmes, this way each haplotype frequency depends on the extent to which mares are involved into the breeding. The reduced number of surviving maternal lineages emphasizes the importance of establishing a conservation plan for this endangered breed. Due to the revealed 34 polymorphic sites we could presuppose twelve maternal linages, which could be a first step for making a breeding programme.